The effect of cyclic stretch on aortic viscoelasticity and the putative role of smooth muscle focal adhesion - Neutel, Cédric H. G.; Wesley, Callan D.; De Meyer, Guido R. Y.; Martinet, Wim; Guns, Pieter-Jan (Frontiers in Physiology, 2023)
Due to its viscoelastic properties, the aorta aids in dampenings blood pressure pulsatility. At the level of resistance-arteries, and transform s the (central) pulsatile flow will be transformed into a (peripheral) continuous flow to allow for optimal perfusion of end organs such as the kidneys and the brain. In this study, we investigated the ex vivo viscoelastic properties of different regions of the aorta of healthy C57Bl6/J adult mice as well as the interplay between (altered) cyclic stretch and viscoelasticity. We demonstrated that the viscoelastic parameters increase along the distal aorta and that the effect of altered cyclic stretch is region dependent. Increased cyclic stretch, either by increased pulse pressure or pulse frequency, resulted in decreased aortic viscoelasticity. Furthermore, we identified that the vascular smooth muscle cell (VSMC) is an important modulator of viscoelasticity, as we have shown that VSMC contraction increases viscoelastic parameters by, in part, increasing elastin fiber tortuosity. Interestingly, an acute increase in stretch amplitude reverted the changes in viscoelastic properties induced by VSMC contraction, such as a decreasing contraction-induced elastin fiber tortuosity. Finally, the effects of altered cyclic stretch and VSMC contraction on viscoelasticity were more pronounced in the abdominal infrarenal aorta, compared to both the thoracic ascending and descending aorta, and were attributed to the activity and stability of VSMC focal adhesion. Our results indicate that cyclic stretch is a modulator of aortic viscoelasticity, acting on VSMC focal adhesion. Conditions of (acute) changes in cyclic stretch amplitude and/or frequency, such as physical exercise or hypertension, can alter the viscoelastic properties of the aorta.